Passive proton therapy vs. IMRT planning study with focal boost for prostate cancer. Issue 1 (December 2015) - Yeo, Inhwan; Nookala, Prashanth; Gordon, Ian; Schulte, Reinhard; Barnes, Stanley; Ghebremedhin, Abiel; Wang, Ning; Yang, Gary; Ling, Ted; Bush, David; Slater, Jerry; Patyal, Baldev
Abstract Background Exploiting biologic imaging, studies have been performed to boost dose to gross intraprostatic tumor volumes (GTV) while reducing dose elsewhere in the prostate. Interest in proton beams has increased due to superior normal-tissue sparing they afford. Our goal was to dosimetrically compare 3D conformal proton boost plans with intensity-modulated radiation therapy (IMRT) plans with respect to target coverage and avoiding organs at risk. Methods Treatment planning computer tomography scans of ten patients were selected. For each patient, two hypothetical but realistic GTVs each with a fixed volume were contoured in different anatomical locations of the prostate. IMRT and proton beam plans were created with a prescribed dose of 50.4 Gy to the initial planning target volume (PTV) including the PTV of the seminal vesicles (PSV), 70.2 Gy to the PTV of the prostate (PPS), and 90 Gy to the PTV of the gross tumor volumes (PGTVs). For proton plans, uncertainties of range and patient setup were accounted for; apertures were adjusted until the dose-volume coverage of PTVs matched that of the IMRT plan. For both plans, prescribed PTV doses were made identical to allow for comparing normal-tissue doses. Results Protons delivered more homogeneous but less conformal doses to PGTVs than IMRT did and comparable doses to PSV and PPS. Volumes of bladder and rectum receiving doses higher than 65 Gy were similar for both plans. However, volumes receiving less than 65 Gy were significantly reduced, i.e., protons reduced integral dose by 45.6 % and 26.5 % for rectum and bladder, respectively. This volume-sparing was also seen in femoral heads and penile bulb. Conclusions Protons delivered comparable doses to targets in dose homogeneity and conformity and spared normal tissues from intermediate-to-low doses better than IMRT did. Further improvement of dose sparing and changes in homogeneity and conformity may be achieved by reducing proton range uncertainties and from implementing intensity modulation.